Synergy of post-2008 Anti-Crisis Policy of the Mild Monetary Policy of the Federal Reserve Bank and the European Central Bank - Dariusz Prokopowicz (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The emergence of the global financial crisis in 2008 has become the reason for the increased use of interventionist economic policy in developed countries in that year. The main instrument of this policy was the significant development of a mild monetary policy and interventionist measures that aim was to force the restructuring processes of heavily indebted enterprises. These measures were used to stop the decline in lending in banking systems. In developed countries, anti-crisis interventionist assistance programs for the financial system and pro-active interventionist measures were activated in order to stimulate significantly weakened economic growth. The costs of saving banks and enterprises from financial bankruptcy have contributed to the increase in debt in the public finance systems of many countries. Analyzes and assessments of government interventionist anti-crisis programs and programs to activate demand, investment, production and liquidity in the credit market have been carried out since 2009. As part of the pro-development activities of the state intervention, the Federal Reserve Bank (Fed) applied a light monetary policy of low interest rates and a program for activating lending and maintaining liquidity in the financial system by financing the purchase of the most endangered assets from commercial banks. A few years later, the European Central Bank (ECB) applied the same activities of activation monetary policy.